Evaluation of Self-Care Practice and Its Associated Factors in Adult Diabetic Patients, Ayder Diabetic Clinic, Mekelle, Ethiopia - Weledegebriel M (Dove Medical Press, 2021)
Migbnesh Weledegebriel,1 Afework Mulugeta,2 Abraha Hailu1 1Department of Internal Medicine, School of Medicine, College of Health Sciences, Mekelle University, Mekelle, Tigray, Ethiopia; 2Department of Public Health, School of Public Health, College of Health Sciences, Mekelle University, Mekelle, Tigray, EthiopiaCorrespondence: Migbnesh Weledegebriel Tel +251914126128Email migbey12@gmail.comBackground: Self-care activities in patients with diabetes mellitus are behaviors undertaken by people with or at risk of diabetes in order to successfully manage the disease on their own. Even though self-care practice plays a critical role in preventing as well as delaying diabetes-related complications, there is poor self-care practice by patients with diabetes mellitus. In Ethiopia, especially in Tigray, there are few studies assessing self-care practice of patients with diabetes mellitus and thus this study will have an input in this area.Objective: To evaluate self-care practice and its associated factors in adult patients with diabetes mellitus having follow-up in Ayder Comprehensive Specialized Hospital, Diabetes Clinic.Methods: A hospital-based cross-sectional analysis was made from March to May, 2015. A total of 410 patients with diabetes mellitus were included. The study participants were selected by a systematic random sampling method. Characteristics of study participants were analyzed using descriptive statistics, while bivariate and multivariable logistic regression was used to identify the association between dependent and independent variables.Results: Two hundred and eighty-eight (70.2%) study participants were above 30 years of age and 254 (62.9%) study participants were males. More than half (52.9%) of the study participants were type-2 diabetes patients. This study showed 207 (50.5%) had poor diabetes self-care practice. In multivariate logistic regression, low income (AOR = 0.518, 95% CI: 0.288– 0.929) and poor knowledge about diabetes (AOR = 5.026, 95% CI: 2.893– 8.734) were found to be significantly associated with poor self-care practice.Conclusion: The proportion of poor self-care practice was high, implying the need for regular follow-up as an integral component of the long-term management of diabetes mellitus.Keywords: self-care practice, diabetes mellitus